Identification of an immune-suppressed subtype of feline triple-negative basal-like invasive mammary carcinomas, spontaneous models of breast cancer. Issue 1 (January 2020) - Dagher, Elie; Simbault, Laura; Abadie, Jérôme; Loussouarn, Delphine; Campone, Mario; Nguyen, Frédérique
Feline invasive mammary carcinomas are characterized by their high clinical aggressiveness, rare expression of hormone receptors, and pathological resemblance to human breast cancer, especially triple-negative breast cancer (negative to estrogen receptor, progesterone receptor, and epidermal growth factor receptor type 2). Recent gene expression studies of triple-negative breast cancers have highlighted their heterogeneity and the importance of immune responses in their biology and prognostic assessment. Indeed, regulatory T cells may play a crucial role in producing an immune-suppressed microenvironment, notably in triple-negative breast cancers. Feline invasive mammary carcinomas arise spontaneously in immune-competent animals, in which we hypothesized that the immune tumor microenvironment also plays a role. The aims of this study were to determine the quantity and prognostic value of forkhead box protein P3-positive peritumoral and intratumoral regulatory T cells in feline invasive mammary carcinomas, and to identify an immune-suppressed subgroup of triple-negative basal-like feline invasive mammary carcinomas. One hundred and eighty female cats with feline invasive mammary carcinomas, treated by surgery only, with 2-year follow-up post-mastectomy, were included in this study. Forkhead box protein P3, estrogen receptor, progesterone receptor, Ki-67, epidermal growth factor receptor type 2, and cytokeratin 14 expression were assessed by automated immunohistochemistry. Peritumoral regulatory T cells were over 300 times more abundant than intratumoral regulatory T cells in feline invasive mammary carcinomas. Peritumoral and intratumoral regulatory T cells were associated with shorter disease-free interval and overall survival in both triple-negative (ER–, PR–, HER2–, N = 123 out of 180) and luminal (ER+ and/or PR+, N = 57) feline invasive mammary carcinomas. In feline triple-negative basal-like (CK14+) mammary carcinomas, a regulatory T-cell–enriched subgroup was associated with significantly poorer disease-free interval, overall survival, and cancer-specific survival than regulatory T-cell-poor triple-negative basal-like feline invasive mammary carcinomas. High regulatory T-cell numbers had strong and negative prognostic value in feline invasive mammary carcinomas, especially in the triple-negative basal-like subgroup, which might contain a "basal-like immune-suppressed" subtype, as described in triple-negative breast cancer. Cats with feline invasive mammary carcinomas may thus be interesting spontaneous animal models to investigate new strategies of cancer immunotherapy in an immune-suppressed tumor microenvironment.